2013
DOI: 10.4049/jimmunol.1301215
|View full text |Cite
|
Sign up to set email alerts
|

Differential T Cell Responses to Residual Viral Antigen Prolong CD4+ T Cell Contraction following the Resolution of Infection

Abstract: The contraction phase of the T cell response is a poorly understood period after the resolution of infection when virus-specific effector cells decline in number and memory cells emerge with increased frequencies. CD8+ T cells plummet in number and quickly reach stable levels of memory following acute lymphocytic choriomeningitis virus (LCMV) infection in mice. In contrast, virus-specific CD4+ T cells gradually decrease in number and reach homeostatic levels only after many weeks. Herein, we provide evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
2
3
0
Order By: Relevance
“…The present results suggest that antigenic signals were not involved in regulating contraction, consistent with findings that the dose and duration of infection do not influence contraction (4,6). Moreover CD8 + T cells do not undergo cell division in response to residual Ag (50), and C3 deficiency does not affect the ability of DCs to present Ag in vitro or during the maturation of DCs in vivo after L. monocytogenes infection (35). In contrast, we found that the levels of critical cytokines, such as IL-12 and IFN-g, were reduced 24 h postinfection.…”
Section: Discussionsupporting
confidence: 78%
“…The present results suggest that antigenic signals were not involved in regulating contraction, consistent with findings that the dose and duration of infection do not influence contraction (4,6). Moreover CD8 + T cells do not undergo cell division in response to residual Ag (50), and C3 deficiency does not affect the ability of DCs to present Ag in vitro or during the maturation of DCs in vivo after L. monocytogenes infection (35). In contrast, we found that the levels of critical cytokines, such as IL-12 and IFN-g, were reduced 24 h postinfection.…”
Section: Discussionsupporting
confidence: 78%
“…Slow contraction of CD4+ T cells paralleled gradual clearance of HAV RNA from the liver over 8–9 months [12,32]. While the continued presence of intrahepatic HAV RNA for such a long period of time was unexpected, it is consistent with a role for residual viral antigen in prolonging CD4+ but not CD8+ T cell contraction as described recently in lymphocytic choriomeningitis virus (LCMV)-infected mice [33]. …”
Section: Adaptive Immunity and Control Of Hav Infectionsupporting
confidence: 57%
“…It is thus tempting to speculate that the capability of CD8 + T cells to respond to a short Ag pulse might reflect transient viral gene transcription and its preferred feeding of the class I pathway. The fact that CD4 + T cells respond much longer to residual Ag following viral clearance than CD8 + T cells do also indicates that antiviral CD8 + T cell responses depend on viral transcription (79,80).…”
Section: Discussionmentioning
confidence: 99%